Peran Patroli Perintis Presisi dalam Mencegah Terjadinya Tawuran di Wilayah Hukum Polda Metro Jaya - Karana, Wahyu Agung Jagat; Nita, Surya; Setyabudi, Chairul Muriman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
The phenomenon of brawls in the DKI Jakarta area is increasing due to environmental, economic, and population density factors in the region. The literature references that form the main basis of this research are situational crime prevention theory, iceberg theory, social conflict theory, youth identity theory, as well as the concepts of community policing, and precision inspector patrols. This research uses qualitative methods with data collection techniques of interviews and document studies. The results showed that the role of the Precision Inspector Patrol in preventing fighting in the jurisdiction of Polda Metro Jaya is to ensure that patrols and general guards can run smoothly, be responsible for each assignment, training, and supervision of patrol teams in other units, be the front guard to carry out various preventive and responsive efforts, conduct routine patrols, respond to reports from the public, and maintain the situation in the jurisdiction of Polda Metro Jaya to remain conducive and under control. Through this role, the strategies that can be carried out by the Metro Jaya Police Precision Inspector Patrol Team in preventing fighting crimes are preemptive, preventive, and repressive strategies that are investigative in nature. The community policing policy model in an effort to maximise the implementation of the Precision Pioneer Patrol to prevent horizontal conflicts in the Polda Metro Jaya jurisdiction can be realised through several management stages which include communication and synergy, cooperation, handling, and performance evaluation. Thanks to this, the Precision Pioneer Patrol has been able to reduce the number of horizontal conflicts that occur in the Polda Metro Jaya jurisdiction. The suggestions are for the Precision Pioneer Patrol Team to increase the frequency of patrols at night in the red and yellow zones, for future researchers to apply GIS as an early detection map of conflict-prone areas, and for cooperation partners to expand the scope of programme implementation P2TP2A Unit, PPA Unit, and FKDM to provide an understanding of the importance of Precision Pioneer Patrol in preventing horizontal conflicts.